Korelasi Antara Fixation Eye Tracking Metric dengan Performance Measurement Usability Testing - Purnomo, Yogie Ajie; Suratno, Tri; Mauladi, Mauladi (JUSS (Jurnal Sains dan Sistem Informasi), 2019)
Not all websites have fulfilled basic principles such as accessible and easy to use (usable). There are several measuring methods that already exist. In this research, the measurement is done by combining 2 measuring methods namely usability testing and eye tracking because the measurement is done with props that are eye tracking, so that at the same time we can measure the indicator usability testing and eye tracking metrics. So researchers to know the level of relationship or correlation between usability testing indicators and eye tracking metrics. The type of research conducted is a type of associative research with quantitative and qualitative approaches. Where both of these methods will result in quantitative data such as time on task, difficulty ratings, fixation duration mean and time to first fixation. Qualitative Data is obtained from playing the recorded results and conducting interviews to examine the results of eye movements when testing is the same as the opinions or perceptions of each participant. Results of a correlation test Pearson product moment acquired correlation or relationship between time on task with fixation duration mean, time on task with time to first fixation, difficulty ratings with fixation duration mean, difficulty ratings with time to First fixation. There are two possibilities of usability measurement performance indicators with eye tracking proving a significant correlation means measurement of usability using eye tracking can be used as an alternative in doing more usability measurement Accurate with significance levels > 2.048 in subsequent studies.